(untitled) (Scientific journal of the Fergana State University, 2023)
The article discusses and analyzes the fact that the creation of electronic (thesaurus), combinatory dictionaries, automation of information related to fields is one of the important tasks today, electronic translator, syntagmatics, combination of language units.